The identity of the invasive yellow-striped terrestrial planarian found recently in Europe: Caenoplana variegata (Fletcher & Hamilton, 1888) or Caenoplana bicolor (Graff, 1899)? - Jones, Hugh D; Mateos, Eduardo; Riutort, Marta; Álvarez-Presas, Marta (Zootaxa, 2020)
Terrestrial planarians with a dorsal yellow stripe and dark lateral surfaces and up to 15-20 cm long have been found in several countries in Europe, the earliest in 2008. They are similar to two species originally from Australia, Caenoplana variegata (Fletcher & Hamilton, 1888) and C. bicolor (Graff, 1899), both described on external characters only, with no anatomical information. Careful reading suggests that there is no significant difference between the original descriptions. Further: observations on live specimens show considerable variation between individuals and in individuals over time and before and after feeding, negating any distinction between descriptions. Examination of three sectioned specimens shows considerable difference in sexual maturity, though one seems almost fully mature and the reproductive system is described. Molecular results show that specimens from the United Kingdom and Spain are of the same species. It is concluded that the planarians should be referred to as C. variegata, C. bicolor being a junior synonym.